2014
DOI: 10.1002/pros.22870
|View full text |Cite
|
Sign up to set email alerts
|

The pluripotency factor Nanog is directly upregulated by the Androgen Receptor in prostate cancer cells

Abstract: Background The Androgen Receptor (AR) is a nuclear hormone receptor that functions as a critical oncogene in all stages of prostate cancer progression, including progression to castration-resistance following androgen-deprivation therapy. Thus, identifying and targeting critical AR-regulated genes is one potential method to block castration-resistant cancer proliferation. Of particular importance are transcription factors that regulate stem cell pluripotency; many of these genes are emerging as critical oncoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 45 publications
(99 reference statements)
1
23
0
Order By: Relevance
“…For example, SOX2 is transcriptionally repressed by AR, and, as expected, treating multiple PCa cell lines with the antiandrogen enzalutamide has been shown to increase SOX2 expression and to lead to CRPC tumor formation (Kregel et al 2013). AR has also been reported to directly bind to the NANOG promoter (Kregel et al 2014) to impart castration resistance in LNCaP cells driven by the expansion of CD133 C and ALDH1 C CSCs (Jeter et al 2011). Apart from direct transcriptional regulation, AR can also indirectly modulate the Wnt (Bisson & Prowse 2009), PI3K/AKT (Dubrovska et al 2009), and hedgehog (Gowda et al 2013) signaling cascades, which play an important role in regulating PCa CSC self-renewal.…”
Section: /Cd133mentioning
confidence: 55%
“…For example, SOX2 is transcriptionally repressed by AR, and, as expected, treating multiple PCa cell lines with the antiandrogen enzalutamide has been shown to increase SOX2 expression and to lead to CRPC tumor formation (Kregel et al 2013). AR has also been reported to directly bind to the NANOG promoter (Kregel et al 2014) to impart castration resistance in LNCaP cells driven by the expansion of CD133 C and ALDH1 C CSCs (Jeter et al 2011). Apart from direct transcriptional regulation, AR can also indirectly modulate the Wnt (Bisson & Prowse 2009), PI3K/AKT (Dubrovska et al 2009), and hedgehog (Gowda et al 2013) signaling cascades, which play an important role in regulating PCa CSC self-renewal.…”
Section: /Cd133mentioning
confidence: 55%
“…And it has been reported that androgen could increase Nanog expression in prostate cancer [19]. These data inspired us to wonder whether the effect of androgen/AR axis on stemness of HCC cells was Nanog depended.…”
Section: Resultsmentioning
confidence: 99%
“…We have further identified multiple E-box elements upstream of NP8 (−133, −486, −1 301, −1 343, −1 437 and −1 607 bp relative to the TSS [1]), suggesting that MYC and NANOG may also form a feed forward cross-regulatory loop. Finally, potential interactions in tumors among AR, NANOG and other pluripotency regulators such as SOX2 (for example, SOX2 has been implicated as an AR-repressed gene that contributes to CRPC [44] and AR has been reported to induce NANOG [45]) may well alter the landscape of the reprogramming dynamics. Future work will aim to elucidate these complicated NANOG interactions and the epigenetic mechanisms whereby NANOG maintains the CSC state.…”
Section: Discussionmentioning
confidence: 99%